Business Environment Analysis in Strategic Management - Milarahma Putri, Dea Wanda; Mila Alvionita; Harly, Muhammad Riadhi; Muhammad Syaifuddin (Journal of Practice Learning and Educational Development, 2025)
The business environment encompasses everything that affects a company's activities and can create opportunities or threats in its operations. Business environment factors consist of two main categories: micro, which involves individuals or parties with direct relationships with the business, and macro, which involves aspects such as economy, demographics, geography, technology, government, social, and political. The increasingly dynamic changes in the business environment and the rising level of competition have affected the sustainability of companies in various sectors, whether large, medium, or small. This research aims to analyze the impact of the business environment on business performance and identify strategies that can be applied to face these challenges. Based on the analysis, the increasingly intense competitive conditions force companies to develop more proactive and innovative strategies, particularly in the marketing aspect. These findings are expected to help the company anticipate changes in the business environment and enhance its competitiveness in the market.